Drivers of Purchase Intention Behavior on Islamic Boarding School (Pesantren) Product at Java Island - Juminten, Rekno; Rusgianto, Sulistya; Isro’i, Moch Imron (IQTISHODUNA, 2024)
This study aims to analyze Halal Perceived Value, Brand Image, and Religious Belief on the purchase intention of Pesantren Products at Java Island. This research uses 132 respondents from consumers who live at Java Island, and who have bought pesantren products. The data collected by the researchers were analyzed using a quantitative approach, with the PLS analysis technique using Smart PLS 4 software. Based on the conclusion that both internal and external factors affecting customers might influence their purchasing behavior on Pesantren products. Internal factors of consumers include religious beliefs and attitudes, and the external aspects include halal perceived value and brand image. Additionally, consumer purchase intentions for pesantren products are unaffected by halal trust, this could be because pesantren products have many competitors with similar products, so even though they are guaranteed halal, they still do not affect the intention to purchase the product. This study found the importance of product halal certificates to increase perceptions of halal values and the brand image of pesantren as a halal industry.